Layout Design for Building Creative Industries in Digitalization Industries 5.0 in Indonesia - Nurani, Nina (Faculty of Law Universitas Padjadjaran, 2024)
DTLST (Integrated Circuits Layout Design) is an open-potential electro-semiconductor technology product developed to build creative industries by effectively protecting IPR as registration. Registration is presently not effectively used, with DTLST violations observed. This study examines the protective patterns of DTLST IPR in building creative industries in the 5.0 digitization industries in Indonesia. A normative juridical method was analytically used, with data collection techniques the literature study primary, secondary, and tertiary legal materials. The results showed that Law no. 32 of 2000 concerning DTLST provided advantages for designers because registration was conducted without a market potential test and affected the legal certainty guarantee of the registrant. However, the arrangement did not accommodate substantive examination, priority rights, and protection of the privilege of owners in good faith. This indicated the necessity for improvement by considering the philosophical factors of justice, balance, and democratic-juridical values regarding the binding power of the regulatory and sociological substance via the living law of the designer. Based on the results, collaboration was needed with the DTLST Office, government, private sector, and universities concerning the use and management of DTLST to build creative industries in the Industries 5.0 era in Indonesia.